Relationship Between Occupants’ Adaptive Behaviors, Air-Conditioning Usage, and Thermal Acceptability Among Residences in the Hot–Humid Climate of Indonesia - Sri Rahma Apriliyanthi; Tomonori Sakoi; Tetsu Kubota; Takashi Nakaya; Mochammad Donny Koerniawan; Muhammad Nur Fajri Alfata; Akhlish Diinal Aziiz; Fefen Suhedi; Inat Shani Fathuna; Taiga Takiguchi (Buildings)
A strategy for effectively utilizing occupants’ adaptive behaviors (OABs) to achieve thermal acceptability while maintaining low energy consumption is necessary. This study aims to clarify the relationship between OABs and thermal acceptability over various climate zones, as well as the change in OABs due to air conditioner (AC) ownership in Indonesian residences. An online questionnaire consisting of perceived OABs’ time intensity, thermal acceptability, and personal attributes from 3000 respondents across Indonesia was analyzed using logistic regression. The results suggested that NV occupants engage in more fan usage and window opening to enhance ventilative cooling, while AC occupants are more likely to adjust clothing and use portable fans to create cooler environments. Moreover, the effects of OABs on NV residences varied depending on the local climate conditions. In hot local climates, averages of 90% fan usage intensity and 92% window opening intensity, complemented with active clothing adjustment, were unable to effectively provide thermal acceptability. These findings imply that there is a range of indoor environmental conditions in which conventional OABs work well. This study highlights the need to promote behavioral adaptations, especially in AC mixed-mode buildings, and to consider behavioral adaptations in NV buildings based on local climates.